A versatile “3M” methodology to obtain superhydrophobic PDMS-based materials for antifouling applications - He, Zhoukun; Yang, Xiaochen; Mu, Linpeng; Wang, Na; Lan, Xiaorong (Frontiers in Bioengineering and Biotechnology, 2022)
Fouling, including inorganic, organic, bio-, and composite fouling seriously affects our daily life. To reduce these effects, antifouling strategies including fouling resistance, release, and degrading, have been proposed. Superhydrophobicity, the most widely used characteristic for antifouling that relies on surface wettability, can provide surfaces with antifouling abilities owing to its fouling resistance and/or release effects. PDMS shows valuable and wide applications in many fields, and due to the inherent hydrophobicity, superhydrophobicity can be achieved simply by roughening the surface of pure PDMS or its composites. In this review, we propose a versatile “3M” methodology (materials, methods, and morphologies) to guide the fabrication of superhydrophobic PDMS-based materials for antifouling applications. Regarding materials, pure PDMS, PDMS with nanoparticles, and PDMS with other materials were introduced. The available methods are discussed based on the different materials. Materials based on PDMS with nanoparticles (zero-, one-, two-, and three-dimensional nanoparticles) are discussed systematically as typical examples with different morphologies. Carefully selected materials, methods, and morphologies were reviewed in this paper, which is expected to be a helpful reference for future research on superhydrophobic PDMS-based materials for antifouling applications.